Managing Tourism Village Potentials through Holistic Approach: Singapadu Kaler Village, Gianyar, Bali - Anak Agung Putu Swabawa; Ni Nyoman Sri Astuti; I Dewa Gede Ari Pemayun (Politeknik Negeri Bali, 2019)
This study aims to design a model for managing the potential of rural tourism in order to empower the potential of tourist attraction and community empowerment in Singapadu Kaler village by using a holistic approach effectively The method used to collect data, there are 4 methods, namely: observation, interview, documentation, and focus group discussion (FGD). Analytical techniques used are: 1) Quantitative analysis techniques, 2) Qualitative analysis techniques, in the form of: a) Descriptive analysis techniques, b) Synthesis analysis techniques, designing a model of tourism village management by considering the potential, effectiveness and feasibility of Singapadu Kaler tourism village which combined with ideas that emerged in the implementation of Focus Group Discussion. The results show that in the village Singapadu Kaler there are three potentials that can be developed into tourism products, namely; 1). natural resources in the form of: river, rice field, and cliff, 2) human resources, 3) cultural resources such as: Kahyanagan Tiga temple, Dang Kahyangan temple, and sacred cultural products. Tourism superstructure that already exist in the form of: business accommodation, restaurant, ATV car business, horse riding business, rubber boat business, swing, and agro business. Regarding the existing tourism infrastructure such as: general infrastructure and basic infrastructure is sufficient. The management model applied is still very partial that has not involved all the existing stakeholders, especially the management of communal tourism products. Regarding the development of tourism villages, tourism village management is closely related to the products produced or offered, and depends on the number of functions in the organization concerned. For this reason, in the management of tourist villages in Singapadu Kaler village holistically, it is necessary to take the following steps: to organize the organizational structure effectively, to put the right people in the management organizational structure that is fairly taken from each hamlet, and to make policies, rules, and schedule of activities based on agreement from all stakeholders involved in the management of Singapadu Kaler tourism village.To achieve sustainable tourism development needs to involve all stakeholders with complemented policies and rules. If necessary engage academics in assistance to design a model of holistic village tourism management